Midterm Outcomes Following Hip Labral Augmentation. Issue 7 (30th July 2021) - Ruzbarsky, Joseph; Arner, Justin; Briggs, Karen; Philippon, Marc; Soares, Rui
Objectives: Arthroscopic hip labral preservation techniques have evolved over the last decade. Arthroscopic hip labral augmentation with iliotibial band (ITB) autograft placed into a labral defect with viable circumferential fibers is a novel treatment option to restore the hip suction seal and improve functionality. The purpose of this study is to determine midterm (3-5 year follow up) outcomes of arthroscopic hip labral augmentation procedure. Methods: Patients who underwent arthroscopic hip labral augmentation from August 2011 to March 2017 were prospectively evaluated. Pre- and post-operative patient reported outcome scores were compared and included SF12 PCS, SF12 MCS, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Modified Harris Hip Score (mHHS), Hip Outcome Score (HOS) (Activities of Daily Living (ADL) and Sport). Post-operative Tegner Activity Scale and patient satisfaction (1 – 10) were also evaluated. Results: One hundred and six patients underwent arthroscopic hip labral augmentation with minimum 3-year follow-up. Mean follow-up was 5-year follow-up (range, 3 to 9.2 years). All patient reported outcomes improved after labral augmentation (SF12 PCS 39±8 vs. 50±10, p>0.01; mHHS 59±15 vs. 79±21, p<0.01; WOMAC 31±16 vs. 16±17, p<0.01; HOS ADL 64±17 vs. 84±21, p<0.01; HOS Sport 41±22 vs. 71±29, p<0.01). Median post-operative Tegner score was 4. Median post-operative patient satisfaction was 9 out of 10 (range, 1-10). In terms of survivorship, 12 patients (11%) required revision surgery and 6 (5.7%) converted to total hip arthroplasty (THA). Conclusions: Arthroscopic hip labral augmentation is a successful treatment option for patients that have viable circumferential fibers present at the time of arthroscopy. This technique continues to show improved patient reported outcomes and is another hip labral preservation technique that may help reestablish the intra-articular fluid suction seal.